Edukasi Tentang Kekerasan Seksual di SDN 1 Sambirejo Kecamatan Wonosalam - Arifin, Zainul; Sayekti, Sri; Meinawati, Lusianah; Adistina, Aimar (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Sexual violence against children is a serious issue that can adversely affect the physical and psychological development of the victim. To prevent this, early education is needed so that children have an understanding regarding physical limitations, their rights, as well as self-protection measures. The purpose of this activity is to provide education towards the understanding of grade 6 students of SDN 1 Sambirejo regarding sexual violence as well as its prevention efforts. These activities were conducted in the form of socialization that included interactive presentations, educational video playbacks, as well as answer discussions. Data were collected through observations and questionnaires before and after socialization to evaluate students’ understanding. / Socialization conducted demonstrated increased students’ understanding of forms of sexual violence, how to protect themselves, as well as actions to take if experiencing or witnessing sexual violence. Education regarding sexual violence prevention is highly effective in raising students’ awareness and needs to be conducted on an ongoing basis involving various parties, including parents and educators.